Сюжет Мертвых душ H.B. Гоголя как барочная метафора - Iwanicki, Aleksander (Acta Polono-Ruthenica, 2018)
A number of the Gogol’s works, he wrote in 1840-s (The Final of "Auditor”, Selected fragments from the correspondence with friends) show a clear connection with the Polish and Ukrainian Baroque tradition of the metaphorical convergence of social and spiritual world. It allows us to suppose the same symbolism in the first part of his poem Dead Souls (1842). Dead serfs that are sold by the landowners to Chichikov as nominally living, can be understood as personality trait of this people that they had lost little by little. It clarifies the sense of the vices that must be showed in the first part of the poem. This is mental stinginess and mental waste, that show themselves by turns in four first figures of the landowners (Manilov, Korobochka, Nozdrev and Sobakevich) and flows together in the last figure of Plushkin.